Annual Report 1989-90 - Planning Commission (Planning Commission, 1989)
The year 1989-90, the terminal year of the Seventh Five Year Plan, has been notable in several respects. Following the general elections in the latter half of the year, new. governments, both at the Centre and in several States, have taken over the reins of office. The composition of the Planning Commission has changed. New Members of the Planning Commission, drawn from distinctive and plural backgrounds, representing an array of achievements, expertise and experience have taken over the task of giving a new shape to the process of planning.
Government of India Planning Commission
Government of India Planning Commission